Delik Pidana Materiil Penipuan Melalui Media Sosial - Setiawan, Hari; Dj. Sidarta, Dudik (UNES Law Review, 2024)
Fraud is a form of general crime in Indonesia according to the Criminal Code. Social media is also developing rapidly with the development of information flow and technology. However, along with the development of the times and the improvement of information and communication technology, fraud is not only carried out directly through face to face, but also through cyberspace/internet or more trendingly through social media. The forms of fraud through social media that occur are quite diverse, including online arisan, investment, and savings and loans, as the author made the thesis material, namely the decision of the Surabaya District Court regarding the decision of the case court fraud via social media. The main issues taken are how the material offense is against fraud through social media and what are the considerations in deciding cases of fraud through social media in question. The research conducted is normative juridical law research. "Normative Legal Research is legal research conducted by examining library materials, both primary data and secondary data. According to article 28 paragraph (1) of RI Law No. 11 of 2008 concerning Information and Electronic Transactions Jo article 45 paragraph (2) of RI Law No. 19 of 2016 concerning Amendments to RI Law No. 11 of 2008 concerning Information and Electronic Transactions Jo Article 64 paragraph 1 of the Criminal Code, the defendant is suspected of having committed a crime if several actions, although each of them is a crime or violation, are connected in such a way that it must be seen as an act that continues intentionally and without the right to spread news lie and mislead which results in consumer losses in electronic transactions. The elements include whoever deliberately and without right spreads false and misleading news which results in consumer losses in electronic transactions and if several actions, although each of them constitutes a crime or violation, are connected in such a way that it must be viewed as one act. continues.